Plot Refugi untuk Pengelolaan Resistensi Hama terhadap Tanaman Transgenik Bt - Bahagiawati Bahagiawati (Jurnal AgroBiogen, 2011)
Refugea Plot as Insect Resistance Management inTransgenic Bt Crops. Bahagiawati. The objective of thisreview is to share information on several cases of targetinsects became resistance to transgenic-Bt crops in the fieldand the refuge strategy used to manage this problem. Btcorn and Bt cotton have been planted widely for severalyears globally. One of the risks of planting transgenic Bt cropis the ability of the target insects adapted to the Bt proteinand caused the resistance breakdown the transgenic Btplants. This phenomenon was hypothesized in early 1990sbased on the cases of several insects resistance to microbialBt sprayed in laboratories and in the field. The mode ofaction of the pest resistance to Bt-toxin have been studied inseveral laboratories. In USA, to avoid the target insectresistance to transgenic Bt crops, a program called InsectResistance Management (IRM) has been applied since 2001for farmers growing Bt crops. Lately, there have been somereports of target insects became resistance to cry1F, cry1Ab,and cry1Ac in transgenic Bt crops. A report informed aboutthe resistance of target insect in Puerto Rico was publishedin 2006, and so in South Africa in 2006/2007, and the last onein India in 2009. To avoid target’s insect become resistanceto Bt crops, a program called structural IRM and unstructuralIRM were introduced and applied in severalcountries. One of the components of IRM is planting refugeplot, a plot that planting with isogenic line of Bt crops in/nearby the area of Bt crops. This review will discuss about thecases of target insect became resistance to Bt crops in thefield, mode of action of insect resistance to Bt, the model ofIRM program in USA and the Philippines and finally therecommendation for Indonesia to prepare its IRM programfor implementing Bt crops.